1993
DOI: 10.1209/0295-5075/21/3/003
|View full text |Cite
|
Sign up to set email alerts
|

C 60 - -Tetraphenylphosphonium + : an Organic Alloy

Abstract: The new fullerite C60−PΦ4+ · (ClPΦ4)2 was investigated by EPR and static susceptibility. Charge transfer from PΦ4 to C60 was found to be incomplete. C60−PΦ4+ separates into a system of localized and delocalized spins at higher temperatures. At 40 K an Anderson-type localization occurs. The low-temperature susceptibility is shown to be a mixture of a Curie susceptibility and a contribution that resembles the behaviour of a spin singlet with an activated low-lying triplet state. The EPR linewidth below 40 K is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…143 139 Early data on phosphonium salts, known to be magnetically dilute from X-ray data, unexpectedly showed excess spin 184 or non-Curie-Weiss behavior. 185,296 Later measurements on both C 60 -and C 70 -salts are, however, in accord with an S ) 1/2 system and Curie-Weiss behavior. 186,190 Ferromagnetic impurities are believed to have been the source of some of the misleading data in the earlier measurements.…”
Section: Magnetic Susceptibility and Spin Statesmentioning
confidence: 78%
“…143 139 Early data on phosphonium salts, known to be magnetically dilute from X-ray data, unexpectedly showed excess spin 184 or non-Curie-Weiss behavior. 185,296 Later measurements on both C 60 -and C 70 -salts are, however, in accord with an S ) 1/2 system and Curie-Weiss behavior. 186,190 Ferromagnetic impurities are believed to have been the source of some of the misleading data in the earlier measurements.…”
Section: Magnetic Susceptibility and Spin Statesmentioning
confidence: 78%
“…55 Although a JT distortion of C 60 − was successfully confirmed, the accuracy of the symmetry identification was limited because a strong counterion vibration obscures the region of the fundamental T 1u ͑1͒ vibration and because no comparison was made to a calculated spectrum. A JT distortion of the C 60 − cage in ͑Ph 4 X͒ 2 C 60 Y materials also was revealed by angulardependent electron spin resonance ͑ESR͒ studies, which found an anisotropic g factor at low T. 33,40,41,43 Among these studies, however, there was no consensus as to whether the specific distortion type was D 2h 40 or a lower symmetry such as C 2h or C i 33 ͑note that neither choice is consistent with the conclusion of the vibrational study 55 ͒. The description of the low-temperature state, the nature of a transition to that state, and the transition temperature have also been the subject of disagreement.…”
Section: Introductionmentioning
confidence: 83%
“…We studied the detailed temperature dependence of the FIR C 60 − modes in ͑Ph 4 As͒ 2 ClC 60 in order to look for an ordering transition reported in previous vibrational, 55 structural, 36,42 and ESR studies 33,40,41,43,47 of the ͑Ph 4 X͒ 2 YC 60 materials. Figures 3͑a͒-3͑d͒ show how the intensity and splitting of C 60 − modes develop with decreasing T. The insets trace the frequency changes with temperature of the inverted peak minima.…”
Section: B Temperature Dependence Of C 60 − Vibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Near infrared-visible spectroscopic experiments on (Ph 4 P) 2 IC 60 show that the electronic and vibrational properties of the C À 60 anion are hardly perturbed by the counterion environment [6]. Detailed temperaturedependent studies of (Ph 4 P) 2 IC 60 have been carried out by electron paramagnetic resonance (EPR) [4,7,8], Raman scattering [9], and infrared spectroscopy [10,11], which demonstrate the dynamic JT effect at room temperature. During cooling down (Ph 4 P) 2 IC 60 undergoes a transition to a static JT distorted state in the temperature range 120-140 K.…”
mentioning
confidence: 99%